Improvements in the metabolic milieu following Roux‐en‐Y gastric bypass and the arrest of diabetic kidney disease. Issue 9 (1st September 2014) - Docherty, Neil G.; le Roux, Carel W.
<x xml:space="preserve">Abstract</x> New Findings What is the topic of this review? This review outlines the indications for use of Roux‐en‐Y gastric bypass as a bariatric and metabolic procedure, addressing the evidence and proposed mechanisms for improvements in the metabolic milieu and blood pressure control. Evidence to date supportive of a role for Roux‐en‐Y gastric bypass in the arrest of diabetic kidney disease follows with a perspective on mechanisms involved and their potential to be replicated in the non‐surgical setting. What advances does it highlight? The review highlights evidence supportive of the potential efficacy of Roux‐en‐Y gastric bypass in preventing progression of early diabetic kidney disease in patients with obesity and type 2 diabetes. Roux‐en‐Y gastric bypass (RYGB) is an efficacious intervention for morbid obesity and has a diabetes‐remitting effect in patients with obesity and type 2 diabetes mellitus, which occurs prior to significant weight loss. Roux‐en‐Y gastric bypass is also associated with early and sustained reductions in the risk factor profile for the progression of diabetic complications. Attention is therefore now being placed on RYGB as a metabolic intervention with the capacity to yield therapeutic benefit in relation to the progression of diabetic complications, such as diabetic kidney disease. As alterations in gut anatomy following RYGB coincide with attendant shifts in downstream enteroendocrine signals with direct and indirect resolutionary effects on the kidney, the concept of an endocrine gut–kidney axis post‐RYGB is growing. With the model of a gut–kidney axis in mind, this article summarizes emerging data on the effects of RYGB on risk factors for diabetic kidney disease (hyperglycaemia, dyslipidaemia and hypertension), highlighting a potential role for glucagon‐like peptide 1 in risk factor reduction.